Strategi Membangun Capaian Pembelajaran Mahasiswa Melalui Internalisasi Nilai-Nilai Perguruan Tinggi - Alimudin, Arasy (DirÃ„ÂsÃ„Ât: Jurnal Manajemen dan Pendidikan Islam, 2017)
In its operation,Narotama University internalizes this value to each membersin the organization, especially the studentsandinvolves them in the development of the value itself, to increase their sense of belonging to the university.Internalization of the value could be a major competitive edge in supporting students attain their maximum learning outcomes. Narotama Universitydevelop a model of value internalization for the aforementionedpupose that are : mappingstudentâs basic character and education assesment, directing them to thelearning outcomes of the study program that suit them best; provides various training and activities that will enhance studentâsemotional and spiritual quotient; nurturing a good student-lecturer communication in the learning process with guidance and consultation until they meet the learning outcomes; conducting an edutainment learning methods with a clear and transparant assesment system.The tracer study results confirmed a success upon the efforts. Graduates of Narotama University are highly employable, 86% of them only takes 0-3 months to get a job. A total of 62.5% of respondents have a job corresponding to their field of study.